Solid Waste Management in Local Municipalities - Criner, George (Maine Policy Review, 1991)
For most of the era since 1960, when environmental policy and resource policy have been central public issues, the focus of public debates on those policies was at the federal and state levels. Now, more and more of the decisions and policies that will determine the quality of life for citizens are being made at the local level. Issues that have historically been local prerogatives are increasingly identified as crucial for effective environmental policy and for insuring "quality of life." Those local decisions are often constrained by a wide variety of state and federal policies on environmental policy and resource use, but effective management of quality of life issues by local governments will clearly require more than reluctant reaction to rules and deadlines imposed from above. In one of a series of three articles in this issue, George Criner examine the match between the increasing demands for local action on environment-related issues and the local resources available to meet those demands, focusing on local solid waste planning